TRADISI PARUNRUNGI BAJU DAN ATTARASA PADA PROSES AKIL BALIG MASYARAKAT KONJO DI BULUKUMBA TIMUR - Khaerun Nisa' (Al-Qalam, 2019)
This study aims to determine the process of implementation the parunrungi baju and attarasa’s tradition in the Konjo community adult process, how is the existance of the parunrungi baju and attarasa’s tradition in the modern area, and how is the islamic perspective on the procession of tradition. The type of this research is qualitative descriptive research. Data sources are primary and secondary data. Researcher as a key instrument. Data collection methods are observation, deep interview and documentation. Parunrungi baju and attrarasa’s tradition is a traditional ceremony held by Konjo community in eastern Bulukumba, when  a child enters adulthood. The traditional still exists carried out by the community of Konjo until now, as a way to appreciate the ancestrals heritage. According to the islamic perpective on the procession of the traditional ceremonies, such as the presentation of offerings and flattening of teeth (attarasa) is considered contradictory to the existing rules in islam.